In Situ Characterization of the Protein Corona of Nanoparticles In Vitro and In Vivo. Issue 38 (16th August 2022) - Latreille, Pierre‐Luc; Rabanel, Jean‐Michel; Le Goas, Marine; Salimi, Sina; Arlt, Jochen; Patten, Shunmoogum A.; Ramassamy, Charles; Hildgen, Patrice; Martinez, Vincent A.; Banquy, Xavier
Abstract: A new theoretical framework that enables the use of differential dynamic microscopy (DDM) in fluorescence imaging mode to quantify in situ protein adsorption onto nanoparticles (NP) while simultaneously monitoring for NP aggregation is proposed. This methodology is used to elucidate the thermodynamic and kinetic properties of the protein corona (PC) in vitro and in vivo. The results show that protein adsorption triggers particle aggregation over a wide concentration range and that the formed aggregate structures can be quantified using the proposed methodology. Protein affinity for polystyrene (PS) NPs is observed to be dependent on particle concentration. For complex protein mixtures, this methodology identifies that the PC composition changes with the dilution of serum proteins, demonstrating a Vroman effect never quantitatively assessed in situ on NPs. Finally, DDM allows monitoring of the evolution of the PC in vivo. This results show that the PC composition evolves significantly over time in zebrafish larvae, confirming the inherently dynamic nature of the PC. The performance of the developed methodology allows to obtain quantitative insights into nano‐bio interactions in a vast array of physiologically relevant conditions that will serve to further improve the design of nanomedicine. Abstract : Most standard characterization techniques cannot capture the subtle complexity of the protein corona. A novel approach using differential dynamic microscopy (DDM) on a simple fluorescence microscope makes possible simultaneous measurements of protein adsorption, particle size, and fractal dimension of aggregates. The new insights obtained from this technique shed light on the protein corona (PC) complexity within in vitro and in vivo setups.